New Perspectives on Embryo Biopsy: Not How, But When and Why? - Xu, Kangpu; Montag, Markus (Seminars in Reproductive Medicine, 2012)
During the past 2 decades, biopsy for preimplantation genetic diagnosis at three stages, that is, before conception (the first polar body), after fertilization (the second polar body), and early cleavage (D3 blastomeres) or blastocyst stage (D5/D6 trophectoderm biopsy), have been optimized and performed clinically in hundreds of in vitro fertilization centers around the world. Although opening the zona pellucida by mechanical or chemical means is still effectively in use, noncontact laser has become the indispensable instrument. Overall, the invasive nature of biopsy at any given stage is recognized. It is believed that removal of the polar bodies from M-II oocytes and fertilized zygotes may have the least detrimental effects on subsequent embryonic development; hence increasing applications of polar body biopsy are anticipated. Although D3 biopsy is currently the most frequently used method, the effectiveness of D3 cleavage-stage biopsy is unsettling because of the mosaicism in early cleavage human embryos. Controversies exist in several areas; particularly, the efficacy of preimplantation genetic screening based on one cell removed from a D3 embryo remains to be confirmed. With new genetic testing technology, there may be no need to biopsy two cells because accuracy from one cell is high and the risk of misdiagnosis is very low when sufficient markers are used for chromosome copy number assessment or for mutation detection of single-gene disorders. And finally, it appears that limited harm is caused by biopsy at the blastocyst stage and mosaicism seems to be less common as compared with earlier stages. Therefore, use of the blastocyst-stage biopsy combined with cryopreservation protocol can be effectively used for several indications. Furthermore, faster genetic analytical methods that can be completed within several hours will make this strategy more practical and attractive as fresh embryo transfer is possible.
Keywords: polar body; blastomere; cleavage embryo; blastocyst; biopsy; PGD